Causes of mortality among whistling ducks in captivity - Hillgarth, Nigella; Kear, Janet (Wildfowl, 1982)
The results of post-mortem data on 983 whistling ducks Dendrocygna dying in Wildfowl Trust collections between 1959 and 1980 have been analysed. The main causes of mortality were tuberculosis, trauma and conditions related to cold sensitivity. There was a very low level of parasite infestation and of aspergillosis.